Human papillomavirus-related mixed non-keratinizing squamous cell carcinoma of the palatine tonsil with small cell neuroendocrine carcinoma: Report of a case. Issue 2 (March 2017) - Ma, Yue; Patil, Ninad; Gagner, Jean-Pierre; Miles, Brett A.
Abstract: Increased testing for human papillomavirus (HPV) in oropharyngeal carcinomas has broadened the range of HPV-associated malignancies identified at this site. While HPV-related oropharyngeal non-keratinizing squamous cell carcinomas (SCC) are known to have a better prognosis than their non-HPV counterparts, HPV positivity may not alter the aggressive nature of HPV-associated small cell neuroendocrine carcinomas (SCNEC). We report a unique case of a mixed non-keratinizing type HPV-associated tonsillar SCC with SCNEC differentiation, and provide a comparison with the rare reported cases of such mixed carcinomas in the literature. Our patient is only the second such case positive for HPV genotype 18 and the only case in which this HPV-related mixed tonsillar tumor occurred in a patient with small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL). The case discussion supports the concept that HPV positivity does not confer a better prognosis in such mixed non-keratinizing type SCC with SCNEC. Our report also alerts pathologists to the need to evaluate for the possibility of a coexisting neuroendocrine component when oropharyngeal squamous cell carcinoma (OPSCC) is diagnosed, as its presence will affect the patients' clinical management and prognosis.